Systematic Review of Common Factors Used to Measure Individuals Career Choice - Azman F.; Abdul Ghapar A.; Ahmad Faudzi M.; Baskaran H.; Rahim F.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Decision making; Career guidance; Career paths; Career selection; Common factors; Decision supports; Prospective study; Research questions; Subjective judgement; Systematic literature review; Systematic Review; Decision support systems